RNases involved in ribozyme degradation in Escherichia coli. - Wang, J Y (1996)
Hammerhead ribozymes are small catalytic RNA molecules that can be designed to specifically cleave other RNAs. These ribozymes have exhibited low efficiency when examined inside cells, perhaps in part because of their sensitivity to intracellular RNases. In an effort to better understand intracellular degradation of small, foreign RNAs and to develop more stable ribozymes, the ability of Escherichia coli RNase mutants to digest ribozymes was examined. In soluble extracts, most (80 to 90%) of the endonucleolytic activity was due to RNases I and I*, since degradative activity was inhibited by Mg2+ and by the rna-2 mutation. Degradation by exonucleolytic activities was temperature sensitive in extracts from an rna pnp rnb(Ts) triple mutant but not in extracts from an rna rnb(Ts) double mutant. Thus, the products of rnb and pnp, RNase II and polynucleotide phosphorylase, respectively, appear to be the major exonucleases that degrade hammerhead ribozymes. Examination of intracellular degradation revealed that RNases I and I* contributed to about half of the degradative activity as judged by comparison of the rate of ribozyme decay in wild-type and rna-2 mutant cells. Little additional effect was observed in rne(RNase E) and rnc (RNaseIII) mutants. Taken together, these data indicate that hammerhead ribozymes are digested largely by the degradative class of RNase (RNases I, I* and II and polynucleotide phosphorylase).